ضوابط الإجتهاد في النص - تطبيقات معاصرة - - يمينة, قداري (University of Eloued جامعة الوادي, 2019)
يتناول البحث جانبًا مهما من مباحث علم أصول الفقه ألا وهو _الاجتهاد والنص_ عالجت طبيعة العلاقة الأصوليَة بين الاجتهاد والنص وبيان دائرة الاجتهاد المشروع الواقع في حضور النص القطعي، والتزويد ببعض الضوابط الحاكة له حال التنزيل، وبيان بعض التطبيقات المعاصرة في ضوء الاجتهاد الواقع في مورد النص، وخلصت أنه لفهم النص وتطبيقه تطبيقاً صحيحاً ضرورة تحقيق المناط فيما يستجد من النوازل الفقهية ليحسن الفقيه تنزيلها على الواقع المتغيـر، وليروم الفقيه الاستمرار في صناعة أحكامها صيانة لمقاصد الشريعة الإسلامية وعدم تحريف النصوص عن مواضعها بالوقوف على العلل التي شرع لأجلها الحكم أصالة، كما أني خلصت أن الاجتهاد في مورد النص لا يُنفى من جميع الوجوه، بل هو ثابت في جميع النصوص بوجه ما، سواء أريد بالنصوص الخطاب: "نصوص الألفاظ القرآن والسنة" أو أريد به نص الدلالة القطعية أي؛ المعاني المستفادة من الألفاظ. "Research Summary The research deals with an important aspect of the study of the fundamentals of jurisprudence, namely ijtihad and the text Dealt with the nature of the fundamental relationship between Ijtihad and the text and the statement of the circle of legitimate Ijtihad in the presence of the text of the cut, And the provision of some of the controls in the case of downloading, , And the statement of some contemporary applications in the light of Ijtihad reality in the resource text, And concluded that to understand the text and its application correctly applied the need to achieve the hypocrisy of new jurisprudence to improve the Faqih downloaded on the changing reality, , And Lairum Faqih continue to manufacture the provisions of the maintenance of the purposes of Islamic law and non-distortion of the texts of their positions by standing on the ills that initiated the rule of authenticity, I also concluded that diligence in the resource of the text is not denied in all respects, But is consistent in all texts in some way, Whether I want the texts speech: ""texts of the Koran and the Sunnah,"" or I want the text of peremptory significance learned from the words. "
مذكرة ماستر خصص فقه مقارن
Keywords: الاجتهاد - موارد النص; Ijtihad- the resource text